Объяснение:
2х + 3у = 7
-5х + 2у = 11 | * -1,5
7,5х - 3у = -16,5
9,5х = -9,5
1)
х = -9,5 : 9,5
х = -1
2)
2*(-1) + 3у = 7
-2 + 3у = 7
3у = 7 - (-2)
3у = 7 + 2
3у = 9
у = 9 : 3
у = 3
Ответ: (-1; 3)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Объяснение:
2х + 3у = 7
-5х + 2у = 11 | * -1,5
2х + 3у = 7
7,5х - 3у = -16,5
9,5х = -9,5
2х + 3у = 7
1)
9,5х = -9,5
х = -9,5 : 9,5
х = -1
2)
2х + 3у = 7
2*(-1) + 3у = 7
-2 + 3у = 7
3у = 7 - (-2)
3у = 7 + 2
3у = 9
у = 9 : 3
у = 3
Ответ: (-1; 3)